Models (form) of long-, medium- and short-term earthquake precursors - Abdullabekov Kakharbay Nasirbekovich; Yusupov Valijon Rustamovich (Geodesy and Geodynamics, 2022)
Through analysis and generalization of more than 50 years of monitoring data pertaining to geomagnetic earthquake precursors in landfills across Uzbekistan involving repeated route and area surveys and stationary observations, as well as extensive data retrieved from the study of the complex in foreign countries, models of long-, medium- and short-term earthquake precursors were created for the first time. Medium- and short-term data were mainly studied based on monitoring data of the precursor complex considering geodynamic polygons in Uzbekistan. The analysis demonstrated that these precursors exhibit different shapes, configurations and signs. There occurred no uniform precursor form. Precursors exhibited bay-shaped forms, including both positive and negative signs, in addition to stepped, wave-oscillatory and other formats. The variety of manifestation forms primarily depends on the surrounding regions' geological and tectonic structures and the various processes in the Earth's crust.